ISLAMIC EDUCATION BASED ON RELIGION MATURITY IN A CROSS-IDEOLOGICAL FRAMEWORK - Abdul Gaffar; Fitriah M. Suud; Riza Zahriyal Falah (IAIN Surakarta, 2021)
This article is a criticism of the Islamic education aspect, which always shown with a model of normative deductive tendencies. Of course, it is an impact on the learners. It is challenging to understand because reviewed full of knowledge that should be skyrocketing grounded, ranging from things that are theocentric to the abstract, tend to ignore the real reality that it is where the students live and interact with people different from themselves. Moreover, the methodology of teaching and learning teachers are comfortable in matters of religion. That is more suitable to be indoctrination and did not effect on dialogic. Indeed, Islamic education should attach continuously to the historical circumstances in which personalities live.